Improving Students' Learning Outcomes in Science and Social Studies Using a Deep Learning Approach with Problem-Based Learning (PBL) Model in Grade IV at SD Negeri 17 Gunung Pangilun, Padang - Irma Apriani Irma Apriani; Etri Wahyuni; Yesi Anita; Ummiatul Fitri (Journal of Education and Teaching Learning, 2026)
This research is motivated by the low learning outcomes of students in Natural and Social Sciences (IPAS) learning in grade IV of SD Negeri 17 Gunung Pangilun, Padang City. This condition is caused by learning that is still centered on teachers, low student involvement, and the lack of optimal implementation of learning models that encourage critical thinking skills. This research aims to improve the learning outcomes of IPAS through the application of the Deep Learning approach with the Problem Based Learning (PBL) model. The research uses the Classroom Action Research (PTK) method with a qualitative and quantitative approach which is carried out in two cycles. Each cycle includes the stages of planning, implementation of actions, observation, and reflection. The research subjects were 18 students in grade IV. Data was collected through observation, interviews, documentation, and learning outcome tests. The results of the study showed an improvement in the quality of learning, as seen from the increase in the assessment of teaching modules from 83.33% to 95.83%. The average learning outcomes of students increased from 58.47 in the first cycle of the first meeting to 73.61 in the second meeting and reached 86.88 in the second cycle. Thus, the Deep Learning approach with the Problem Based Learning model is effective in improving the learning outcomes of social studies of students.